Hybrid Corn Business Development Strategy In Wailola Village, Bula District Seram District - Inn Ruusukun; A ugust E Pattiselanno; Jeter D. Siwalette (Cita konsultindo, 2023)
The purpose of this study was to determine the strategy for developing farming in Wailola Village, Bula District, East Seram District. Determining the sample of farmer respondents using Simple Random Sampling , with as many as 25 farmer respondents . The results showed that the strategy for developing farming in Wailola Village, Bula District, East Seram Regency used the SO strategy, where this strategy was used to take advantage of existing strengths and opportunities to minimize weaknesses and threats by optimizing land use with existing skilled workforce and establishing good communication. between farmers, the government and traders for marketing information. Factors that influence the development of corn farming in Wailola Village, Bula District, Eastern Seram Regency are internal factors which include: Availability of a large area for corn development, land conditions that support corn cultivation, availability of skilled labor , adequate transportation facilities, does not require special expertise in cultivation, and external factors, including: market demand is quite large, agro-climate land that is good enough for corn cultivation, corn farming that can provide benefits, OPT disturbances.